Copyright Law Regulatory Framework for NFT collections Transactions: Origins, Controversies and Approach Exploration - Luo, Han; Du, Tinghuan (Technium Social Sciences Journal, 2024)
NFT collections are the result of the convergence of blockchain and smart contract technology with a specific digital content, comprising a technology layer and a content layer. The fundamental aspect of NFT collections is the usufructuary right to the digital content. The aforementioned digital content is copyrightable, which may in turn result in the trading of NFT collections being subject to copyright laws. The sale and transfer of collections can be considered to exist along three distinct appraoches of regulation: the right of distribution, the right of communication through information network, and non-infringement. It can be argued that collections are not objects of ownership. Thus, the nature of their usufruct does not unduly interfere with the proprietary style of copyright. Consequently, it could be proposed that the sale and transfer of collections cannot be subject to distribution rights regulation, either directly or by analogy. The approach of non-infringement presents significant systemic challenges in the context of legal application and fails to address the need for formalization of industry development. The sale and transfer are consistent with the constituent elements of the act communication through information network and can effectively overcome the inherent disadvantages of the aforementioned path. Therefore, it should be adopted. With regard to the additional burden of authorization created by the approach, the industry can achieve relief through the introduction of industry self-regulatory conventions or guidelines, and so on.